Keragaman Fenetik Pisang Lokal yang Dimanfaatkan oleh Masyarakat Sentani Kabupaten Jayapura, Papua - Lisye I. Zebua; Vita Purnamasari; Mariana Ondikeleuw; Geofani A. Lobo (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
Banana plants are a food source that has good prospects. This is because bananas are very popular with all groups, and are easy to grow in tropical areas. There are many varieties of wild and cultivated bananas that grow in Indonesia, one of which grows around Lake Sentani, causing differences in morphological characters between types and between varieties of bananas. The purpose of this study was to determine the phenetic diversity of local Sentani bananas based on morphological characters. The research was conducted in June-October 2022 in five villages around Lake Sentani, namely Ayapo, Yahim, Kampung Harapan, Doyo and Netar using the exploration method and interviewing key informants. For morphological identification using banana descriptor guidelines from the International Plant Genetic Resources Institute (IPGRI). Morphological character data were analyzed in a quantitative descriptive manner using the NTSYs 2.01 application program. The results showed that there were 15 local banana cultivars based on the knowledge of the Sentani people. Based on the phenogram, the local Sentani bananas are grouped into two groups based on the character of the shape, size, color, taste, and color of the organs of the leaves, stems, flowers and fruit. The local banana cultivars have wide phenetic diversity with similarity coefficient values ranging from 20-73%. The closest similarity value is found in Hoyombi and Wabulu cultivars with a similarity value of 73%. The furthest similarity value was found in the Rawo and Anakhola cultivars in group A, and the Olukhu and Honggambu cultivars in group B with a value of 53%. Key words: diversity; characters; morphology; bananas; Sentani.